Effective Delivery of Pressure Training: Perspectives of Athletes and Sport Psychologists - Low, W. R.; Butt, J.; Freeman, P.; Stoker, M.; Maynard, I. (The Sport Psychologist, 2022)
Pressure training (PT) strategically increases pressure in training to prepare athletes to perform under pressure. Although research has studied how to create pressure during training, PT`s effectiveness may depend on more than creating pressure. A practitioner`s delivery of sport psychology interventions can moderate their effectiveness, so the current study explored perspectives of sport psychologists and athletes on the characteristics of effective PT delivery in applied settings. Eight international-level athletes and eight sport psychologists participated in semistructured qualitative interviews in which they described their experience participating in or conducting PT, respectively. Thematic analysis produced four themes relating to effective delivery: (a) collaboration with athletes and coaches: "with," not "to"; (b) integration into training; (c) upfront transparency; and (d) promoting learning before and after PT. The themes provide guidance for planning, conducting, and following up on PT sessions in applied settings. The best practices discussed could increase athletes` receptiveness to PT.